Образ княгині Ольги в “Синопсисі Київському” - Щербак, О. (Слово і Час, 2018)
У статті проаналізовано художньо-історичний образ княгині Ольги в “Синопсисі Київському”.
Хоча ця пам'ятка другої половини XVII ст. рясніє промосковськими мотивами, однак образи
руських правителів цікаві з літературного погляду. Зокрема, виявлено, що зображення княгині
Ольги, близьке до російської “Ступеневої книги”, тяжіє до художнього осмислення її постаті,
ролі в історії й навіть рис характеру. Також з'ясовано, що автор змалював Ольгу, яка жила
у Х ст., крізь призму свідомості монаха-книжника XVII ст. The paper analyzes the historical and literary image of Princess Olha in “Synopsis of Kyiv”.
“Synopsis of Kyiv” was repeatedly criticized for its strongly marked pro-Russian motives. The analysis
of all versions of this work may expose new facts that will help us to take an open-minded look at
it. The ambiguous political tendencies of “Synopsis of Kyiv” can’t overshadow its high literary value
and originality against the background of contemporary literature of Ukraine. Anyway, it is one of the
last works of the Old Ukrainian literature that offers rather unbiased view on the medieval history of
Ukraine and provides arguments for talking about its independence.
Amongst all Kyiv princes the author marks out the prince Volodymyr the Great and his grandmother,
the first Christian woman in Kyivan Rus, Princess Olha of Kyiv.
Princess Olha might be the only woman of power in Ukrainian history, therefore being a distinct
personality in the old literature. No other woman of the world was honored so highly by the Kyivan
Rus authors, and no other woman was awarded with such amount of literary information, even though
most ‘facts’ of her biography were legends and exaggerations. After all Olha is one of the few women
in Ukrainian history who are known abroad, where, of course, she doesn’t have such a fame not being
a sacred historical figure.
Of course, the stories about Olha in “Synopsis of Kyiv” are not original; the work was greatly
infl uenced by “The Tale of Past Years”, hagiographical stories from the Hustynia Chronicle, and
“Chronicle” by F. Sofonovych. But having gathered all that material the author created a new version
of the story. It is discovered that the portrayal of Olha, which was close to the one in the Russian “Book
of Royal Genealogy”, is created by the author with much attention to her role in history and even her
personal character traits. It is also proved that the author, being the 17th century monk, portrayed
Olha, who lived in the 10th century, from his own point of view. Статья посвящена детальному анализу художественно-исторического образа княгини Ольги в “Киевском синопсисе”.
Хотя созданный во второй половине XVII в. “Синопсис” изобилует
промосковскими мотивами, образы русских правителей,
представленные там, интересны с литературной точки зрения.
В частности, выявлено, что изображение княгини Ольги, близкое
к российской “Степенной книге”, тяготеет к художественному
осмыслению автором ее фигуры, роли в истории и даже личных
черт характера. Также установлено, что автор изобразил Ольгу,
жившую в Х в., сквозь призму сознания монаха-книжника XVII в.